Assessment of nurses' self esteem from their own point of view - Valentukevičiūtė, Inga; Blaževičienė, Aurelija (Slauga. Mokslas ir praktika, 2022)
Investigation problem. The self-esteem of nurses in today's context is extremely important in order to ensure the provision of quality services to patients. It is noticed that low self-esteem prevails more and more often among specialists in various fields. It often becomes an obs-tacle in order to maximally implement the set goals of organizations and ensure high-quality services.Aim. To assess nurses' self-esteem from their own point of view.Methods. The applied method is an anonymous questionnaire survey. The standardized Rosenberg self-esteem assessment scale was used for the study.Subjects. General practice nurses working in hospitals providing secondary level care.Conclusions. After analyzing the data obtained during the study, it became clear that nurses usually had average self-esteem. It is observed that nurses with less work experience more often rate their self-worth as high. Also, the number of nurses with high self-esteem was among those who worked less than 1.0 full-time.
Keywords: Self-esteem; nurses; hospitals